Dilemma in laboratory diagnosis of Dengue, Chikungunya and Zika viruses - Ahmed, Mushtaque; Mahboob, Nabeela; Mamun, Kazi Taib; Iqbal, Hasina (Bangladesh Journal of Medicine, 2019)
Dengue, Chikungunya and Zika are the vector-borne diseases that constitute a potential epidemiological risk due to the recent increase in cases, complications, and severity. The co-circulation of the three diseases is a matter of public health interest due to their transmission by the same vector as well as the increase in the number of cases of severe dengue hemorrhagic fever, post-chikungunya chronic joint disease and microcephaly related to Zika virus. Therefore, it is important to be familiar with the various clinical presentations and laboratory methods to make the differential diagnosis, start appropriate treatment, and prevent the associated complications. Bangladesh J Medicine July 2019; 30(2) : 83-92